UJI KETAHANAN JAGUNG HIBRIDA TERHADAP KARAT DAUN DI SULAWESI SELATAN DAN PARE KEDIRI - hendrayana, Febri; Christie, Chitra Dewi Yulia; Lestari, Nia Agus; Tasbi, Julaeha (Jurnal Agriovet, 2025)
One of the strategic steps that must be taken to maintain a steady increase in maize production and distribution in Indonesia is to provide high-yielding varieties that are resistant to biotic and abiotic stresses, and have wide adaptation in various ecosystems. The aim of this research is to produce and release adaptive hybrid maize varieties with high productivity. Testing for leaf rust disease resistance (Puccinia polysora) was conducted in a randomized group design, with 3 replications. The genetic material used was the same as the adaptation test material in the form of 8 test hybrids namely BPN2301, BPN2302, BPN2303, BPN2304, BPN2305, BPN2306, BPN2307, BPN2308, and 2 comparison varieties namely NK6172 and BISI 18. The leaf rust disease resistant check variety used the Pertiwi 6 variety, while the susceptible check used the Pulut URI 1 variety. The results obtained can conclude that the results of the resistance test of 8 hybrid corns, namely Pulut URI 1 variety is very susceptible to leaf rust disease, BPN2303 and BISI 18 are classified as susceptible to leaf rust disease, while other varieties are somewhat resistant to leaf rust disease.